Cultura Analysis in the Nyorong Tradition as Social Solidarity and Ethnopedagogical Perspective - Andriani, Heni; Bilal, Arpan Islami; Muhdar, Syafruddin (Institut Agama Islam Negeri Kendari, 2026)
This study aims to analyze the social, cultural, and educational values within the Nyorong tradition of the Sumbawa community in Kebayan Village, Brang Biji Subdistrict, Sumbawa Besar Regency, and to examine its implications as a source of ethnopedagogical learning. This study employs a descriptive qualitative approach, utilizing data collection techniques such as observation, in-depth interviews, and documentation. Data analysis was conducted using the Miles and Huberman interactive model, which includes data collection, data reduction, data presentation, and drawing conclusions. The results indicate that the Nyorong tradition is still practiced as part of the Sumbawan traditional wedding ceremony and functions as a social mechanism that strengthens solidarity, cooperation, and collective community participation. Beyond serving as a traditional ritual, the community’s direct involvement in this practice creates a contextual social learning space that enables the natural internalization of moral, social, and cultural values among the younger generation through direct experience. Based on the analysis, the concept of ethnopedagogy in this study is derived from the patterns of social interaction and the process of value transmission that occur in practice within this tradition, indicating that learning takes place not only formally but also through the community’s cultural practices. The findings of this study confirm that the Nyorong tradition serves as a source of character education rooted in local wisdom, thereby strengthening culture based education. The uniqueness of this study lies in its exploration of the mechanisms through which values are internalized within the Nyorong tradition as a form of ethnopedagogy grounded in the community’s social practices.